Detection of Plasmodium falciparum malaria by 16S rDNA testing in pericardial fluid from a blood antigen and microscopy negative patient - Joseph J. Zeppa; Andrew K. Kapoor; Deborah Yamamura; Mark Loeb; Antoine Corbeil; Julianne V. Kus (ASM Case Reports, 2026)
ABSTRACT Background Malaria is typically diagnosed using rapid antigen tests and microscopy. This case describes an unusual presentation of Plasmodium falciparum , initially detected via 16S rDNA testing of pericardial fluid identifying apicoplast DNA—a finding not previously reported in the literature. Case Summary A septuagenarian Nigerian man visiting Canada presented with shortness of breath, tachycardia, tachypnea, anemia, and a pericardial effusion. Pericardiocentesis yielded serosanguineous fluid, and imaging revealed multifocal opacities. Blood and fluid cultures were negative for bacterial organisms. After briefly leaving the hospital against medical advice, he returned in respiratory distress and required intubation for acute respiratory distress syndrome. He received empiric antibiotics for rickettsial infection (due to positive serology) and presumed sepsis. Further workup, including pericardial fluid 16S rDNA PCR and sequencing, identified P. falciparum apicoplast DNA. This was confirmed by malaria antigen and Plasmodium -specific PCR testing of the fluid alongside PCR of whole blood, though microscopy and antigen tests remained negative. Hemozoin-like structures were also identifiable in the pericardial fluid. He was treated with a 3-day course of atovaquone-proguanil for malaria, with subsequent clinical improvement. He remains well on follow-up. Conclusion This case underscores an uncommon presentation of P. falciparum and, though not a standard or recommended diagnostic tool for malaria, in this case, 16S rDNA analysis aided in the diagnosis. Clinicians should maintain malaria in the differential for patients from endemic regions. Multidisciplinary collaboration was essential in achieving the diagnosis.